The Reform of Timor Leste’s Investment Law in The Concept of The Welfare State - Eugenia Brandao da Silva; Iman Prihandono; Yuniarti Yuniarti (JURNAL AKTA, 2026)
Foreign direct investment (FDI) is one source of funding for national development. However, its application in Timor-Leste is currently still limited. FDI accounts for 45% of total domestic investment, while domestic investment (NDI) accounts for 55%. This shows that the country's main economic sector is still dominated by oil and gas. Legal and regulatory barriers are one of the main obstacles to attracting foreign investment, even though FDI has the potential to drive sustainable economic growth and improve people's welfare. However, reform is still needed in the Investment Law to emphasise that investment, including FDI, is not only about economic growth, but also a constitutional tool to achieve public welfare through job creation, strengthening public services, and protecting vulnerable groups. This research is normative in nature, analysing various laws and regulations applicable in Timor-Leste. Primary data was obtained from laws, regulations and government policies related to investment, while secondary data was sourced from books, journals and other relevant scientific literature. The findings show that investment barriers in Timor-Leste include a complicated bureaucratic licensing process, fragmented regulations, limited human resource capacity, inadequate infrastructure, and a small domestic market. Furthermore, foreign investment laws are not in line with the Timor-Leste Constitution in terms of achieving prosperity. These conditions have an impact on the investment climate and economic growth, which are not yet optimal in realising a welfare state. The results of the study emphasise the importance of integrated regulatory reform, such as simplifying licensing procedures, increasing legal certainty in investment, and adjusting national policies to Timor-Leste's international standards in the field of trade and investment.